1994
DOI: 10.1080/17450399409381773
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for the introduction of an energetic feed evaluation system based on unitary parameters and principles for all farm animals

Abstract: The energy availability from the feedstuffs and the energy requirement of animals are characterized by the metabolizable energy. The metabolizable energy of the feed (feedstuff, ration) is interpreted as potential energy. For comparative analyses within and between animals species with regard to the energetic feed value of single feedstuffs the parameter "relative fat retention effect" is introduced. The metabolizable energy of a ration is estimated in consideration of live weight and protein production (prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Many authors (Whittemore et al, 1995;Sinclair et al, 1998) have found that a fat layer whose thickness exceeds 16 mm leads to good reproductive results. High-calorie flush feeding a few days before oestrus appears in gilts has a beneficial effect on the intensity of ovulation (Hoffmann, 1994;Van den Brand et al, 2001). …”
Section: Resultsmentioning
confidence: 99%
“…Many authors (Whittemore et al, 1995;Sinclair et al, 1998) have found that a fat layer whose thickness exceeds 16 mm leads to good reproductive results. High-calorie flush feeding a few days before oestrus appears in gilts has a beneficial effect on the intensity of ovulation (Hoffmann, 1994;Van den Brand et al, 2001). …”
Section: Resultsmentioning
confidence: 99%